2019
DOI: 10.1002/pol.20190165
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of well‐defined block copolymer composed of flexible amphiphilic poly(ethylene glycol) and hydrophobic liquid crystalline segments by living coordination polymerization of allene derivatives and its application to thin film with perpendicularly oriented cylindrical nanostructure

Abstract: A block copolymer composed of a flexible polar poly(ethylene glycol) (PEG) and a less polar liquid crystalline poly(allene) segments is prepared by the living coordination polymerization of an allene derivative possessing transazobenzene-containing mesogenic substituent by the use of a π-allylnickel macroinitiator bearing PEG segment. The thin film of the block copolymer is prepared by the spin coating of its solution onto mica or silicon wafer which proves to possess perpendicularly oriented nanocylindrical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…The authors further demonstrated incorporation of a hydroxyl bearing allene comonomer that was subsequently used for postpolymerization modification, altering the hydrophilicity of the microspheres (Figure C). Sakai et al also used monosubstituted allene derivatives to make block copolymers consisting of polyethylene glycol and polyallene blocks and used these to prepare a thin film consisting of perpendicular nanocylindrical structures. One of the few properties of polyallenes that have been reported is the crystallinity of the polymers; a recent study from Lin et al illustrated high crystallinity of polyallenes which have high regularity of the backbones (strictly 2,3-polymerization) …”
mentioning
confidence: 99%
“…The authors further demonstrated incorporation of a hydroxyl bearing allene comonomer that was subsequently used for postpolymerization modification, altering the hydrophilicity of the microspheres (Figure C). Sakai et al also used monosubstituted allene derivatives to make block copolymers consisting of polyethylene glycol and polyallene blocks and used these to prepare a thin film consisting of perpendicular nanocylindrical structures. One of the few properties of polyallenes that have been reported is the crystallinity of the polymers; a recent study from Lin et al illustrated high crystallinity of polyallenes which have high regularity of the backbones (strictly 2,3-polymerization) …”
mentioning
confidence: 99%